Realization and Nash Implementation: Two Aspects of Mechanism Design - Williams, Steven R. (Econometrica, 1986)
In this paper we will show how a message process which "realizes" (or computes) a given social choice rule F can be used to construct a game which implements F in Nash equilibrium. Any efficient encoding of information that occurs in the message process causes a corresponding reduction in the size of the strategy space of the game which we will construct to implement F. Necessary and (stronger) sufficient conditions on the message process will be given for this construction.